Pre-service teachers’ mathematical concepts in indigenous languages: Challenges encountered in multilingual classrooms, Rundu urban, Namibia - Nahole, Martha; Haimbodi, Frans Ndemupondaka (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2022)
Teaching mathematics in primary schools using indigenous languages as the language of instruction may present a professional challenge for teachers in several ways. Whereas most studies focused on teachers’ use of indigenous language in mathematics classrooms, there seems to be little done on the challenges experienced by pre-service teachers while teaching mathematics in indigenous languages. This study, thus, explored the challenges experienced by pre-service teachers teaching mathematics in indigenous languages at the primary school phase in Namibian multilingual classrooms. The study used a total population sampling technique and involved 90 pre-service teachers at the Rundu campus of the University of Namibia who voluntarily completed the questionnaires. The results showed that pre-service teachers faced difficulties with some concepts that were rather literally translated from English to vernacular. Thus, the translation led to ambiguous meanings. Another challenge was that some of the learners had problems in understanding the concepts in the language of instruction as they had a different mother tongue, for example the Chokwe and Nyemba speaking learners in classes where the medium of instruction is Rukwangali.